(untitled) (Experimental biology, 2015)
Basic curative properties of glycyrrhiza root are conditioned mainly by glycyrrhizic acid and its aglycone – glycyrretic acid. These glycosides and their different derivatives possess the wide spectrum of biological activity.Antiinflammatory effect of glycyrrhizic acid and glycyrretic acid is connected with their and its cortizolic effect, which is the inhibition of phospholipase A2. This enzyme breaks down lipids in cell membranes, thereby starting the process of accumulation of proinflammatory prostaglandins and leukotrienes. In addition to this effect, glycyrrhizin also inhibits the formation of prostaglandins.Glycyrretic acid being, a sinergistom of cortisone, is able to inhibit the metabolism of reductase and corticoid hormones in the body. Reducing the activity of the reductase, it leads to an inhibit excretion of corticosteroids, and in such a way increases the duration of their action. Action like corticosteroids and pharmacological activity of glycyrrhizic acid and glycyrretic acid can be explained by the fact that certain elements of the structure are very similar to the structure of corticosteroid hormones.